Issues and Strategies of Natural Resource Management and Land Use Planning in Semi-arid Regions of India - Singh, S K; Patil, N G; Tiwary, P; Chatterji, S (Annals of Arid Zone, 2016)
In Indian context, land use planning is usually centred on agricultural land use and livestock management with peripheral window for common property resources and non timber forest produce. National Bureau of Soil Survey and Land Use Planning (NBSS&LUP) has delineated the country into different agro-ecological regions (AER) based on four parameters soil, physiography, length of growing period (LGP) and bioclimate. This article dwells on the land use planning issues and strategies of semi-arid region that covers 101 Mha area of the country. It is home to more than 341 million human population spread in 175 administrative districts. The region has very little area under forest (10%). There are many intra-regional variations that entail different strategies for agricultural development or land use planning. In AER 4, 164 million people reside, which is almost 50% of the total population in semi-arid region. Because the per capita land availability is lowest in this part of India, it is pertinent that the land resources cannot be expected to provide sustenance unless land use changes substantially from agriculture to more rewarding, employment generating activity. In AERs 7 and 8 the net sown area is relatively low, therefore there appears to be land availabe that could be utilized for developments such as pasture lands, agro-forestry development etc. Current utilization status of four main resources namely land, water, forest and livestock is discussed to identify potential for development in each sector. We argue that land resource inventory needs to be developed for this purpose. Modern tools that could be employed for inventorization of soil resources are also discussed. Key words: Land use planning, semi-arid region, land resource inventorization, agro-ecological region, soil survey.